New Routes for Refinery of Biogenic Platform Chemicals Catalyzed by Cerium Oxide-supported Ruthenium Nanoparticles in Water. Issue 1 (December 2017) - Mizugaki, Tomoo; Togo, Keito; Maeno, Zen; Mitsudome, Takato; Jitsukawa, Koichiro; Kaneda, Kiyotomi
Abstract Highly selective hydrogenative carbon–carbon bond scission of biomass-derived platform oxygenates was achieved with a cerium oxide-supported ruthenium nanoparticle catalyst in water. The present catalyst enabled the selective cleavage of carbon–carbon σ bonds adjacent to carboxyl, ester, and hydroxymethyl groups, opening new eight synthetic routes to valuable chemicals from biomass derivatives. The high selectivity for such carbon-carbon bond scission over carbon-oxygen bonds was attributed to the multiple catalytic roles of the Ru nanoparticles assisted by thein situ formed Ce(OH)3 .